(untitled) (Bangladesh Journal of Botany, 2018)
Carum copticum L. comprises several relevant species for food, cosmetic, perfumery and pharmaceutical industries. GC/MS analysis of the enential oil of C. copticum revealed γ- terpinene as a major component of C. copticum, with its contribution of 33.85%. Essential oils (EOs) exhibited a significant antimicrobial activity against all tested microbial strains. In addition, the C. copticum oil demonstrated the highest DPPH radical scavenging activity. These results clearly show the antimicrobial and antioxidant effects of the plant essential oil.